Chemistry and fabrication of polymeric nanofiltration membranes: A review. (26th October 2016) - Paul, Mou; Jons, Steven D.
Abstract: The review article describes research on different methods for manufacturing polymeric NF membranes. The primary focus is on NF composite membranes formed by interfacial polymerization. Within that space, topics covered in detail include the composite structure, monomeric and polymeric reactants employed to endow specific characteristics, and additives used to influence the reaction. Other approaches covered that have been commercially important are manufacture of NF membranes by phase inversion and different post-treatments (e.g. coatings, grafting) that may be applied to a more porous support. Emerging technologies also discussed include layer-by-layer coatings, incorporation of aquaporins, and use of glassy polymers with high internal porosity. Common themes include research directed to improved performance (flux, rejection, selectivity, reduced fouling) and modifications that allow for success in more challenging feeds (pH extremes, high temperature, chlorine, solvents). Graphical abstract: Highlights: Review (537 references) focusing on chemistry of polymeric nanofiltration membranes. Emphasis on interfacially polymerized NF composite membranes. Discusses composite structure, reactants, additives, and post treatments. Identifies need for improved uniformity of membrane testing within NF field.